You're not supposed to die tonight ebook - Bayron, Kalynn (2023)
Instant New York Times bestseller! At Camp Mirror Lake, terror is the name of the game . . . but can you survive the night? This heart-pounding slasher by New York Times bestselling author Kalynn Bayron is perfect for fans of Fear Street . Charity has the summer job of her dreams, playing the "final girl" at Camp Mirror Lake. Guests pay to be scared in this full-contact terror game, as Charity and her summer crew recreate scenes from a classic slasher film, The Curse of Camp Mirror Lake . The more realistic the fear, the better for business. But the last weekend of the season, Charity's co-workers begin disappearing. And when one ends up dead, Charity's role as the final girl suddenly becomes all too real. If Charity and her girlfriend Bezi hope to survive the night, they'll need figure out what this killer is after. As they unravel the bloody history of the real Mirror Lake, Charity discovers that there may be more to the story than she ever suspected . . .